Quality of Care in Pediatric Palliative Care: A Scoping Review - Tania Ruiz-Gil; Francisco Ródenas-Rigla (MDPI AG, 2023)
Palliative care (PC) enhances the quality of life for patients and families facing life-threatening conditions. While PC is well-established for adults, not all practices apply to pediatrics. Consequently, specific quality indicators for Pediatric Palliative Care (PPC) must be identified. This scoping review aimed to identify the variables associated with the quality of care of PPC patients in Spain, focusing specifically on three areas: structure and process of care, psychological aspects of care, and care of patients approaching the end of life. The review was conducted following PRISMA-ScR guidelines. Searches were performed in the PubMed, Scopus, Web of Science, Embase, ProQuest, and Dialnet databases covering the period extending from January 2000 to May 2023. Finally, 35 studies were identified for the complete review. A total of 30 studies include variables associated with the structure and process of care, 20 include variables associated with psychological aspects of care, and 23 studies integrate variables related to patient care at the end of life. Analysis suggests that enhancing professional training in aspects such as communication with patients and families, creating intimate spaces with flexible visiting hours, increasing emotional support, promoting frequent contact with healthcare teams, and transparently communicating about illness and imminent death to both families and minors could improve the quality of PPC.